The Role of Self-Efficacy in Enhance Metacognitive and Academic Performance Through Problem-Solving - Anggraini, Elisa; Subanji, Subanji; Rahardjo, Swasono (Universitas Suryakancana, 2024)
This research analyzes the role of self-efficacy in enhancing metacognitive and academic performance of students through problem-solving as learning process. Researchers research some students from senior high school in Malang. This research uses mixed methods with surveys, interviews, and analysis of students’ learning outcomes. At the first meeting, students were asked to fill survey about the dimensions of self-efficacy, which are magnitude, strength, and generality. Moreover, researchers interviewed students to explore their metacognitive activities that they do, such as awareness, regulation, and evaluation. After that, researchers analyze their learning outcomes to determine their academic performance. This research result shows that students with a high dimension of self-efficacy tend to show better metacognitive activity than the other. Furthermore, students with a high dimension of self-efficacy tend to show better academic performance than others.